Effect of mining site seepage and copper plant waste water on the water quality and epilithic diatom communities in Maden Stream (Elazig-Turkey) - Yildirim, Vesile; Kulkoyluoglu, Okan (C M B Assoc, 2018)
The present study investigated the effect of pollution caused by mining site seepage, copper plant flotation and domestic wastewaters on the water quality and epilithic diatom communities in the Maden Stream, Elazig (Turkey). Maden Stream's epilithic diatoms, water chemistry and physical variables were examined between January 2008-December 2008 which identified 4 stream sites taken the samples of montly periods. During the study, a total of 77 diatom taxa belonging to 24 genera were identified. Three of which Cymbella, Navicula, and Nitzschia included the highest number of species. Species dominancy was changed among the stations where the most common species found from first, second, third, and fourth stations were Cymbella affinis, Ulnaria ulna, Achnanthes minutissima and Surirella angustata, and Gomphonema parvulum, respectively. Canonical correspondence analysis (CCA) explained 82.6% of the correlation between 66 species and 12 environmental variables among which EC, pH, DO, and Mn, were the most explanatory variables for species occurrence. Individual species showed different ecological tolerance and optimum levels. Among the species with cosmopolitan characteristics, eight of them (C. cistula, U. ulna, Nitzscia palea, N. sigmoida, G. parvulum, Achnanthes laceolatum, Navicula pupula, and Diatoma tenuis) were the most common species with relatively high tolerance levels to those environmental variables measured.
Keywords: Epilithic diatoms; Water quality; Heavy metals; Diversity; Pollution